HUBUNGAN PENGETAHUAN TENTANG TUMOR PAYUDARA DENGAN KECEMASAN PADA REMAJA PUTRIâ€ ( STUDY KASUS DI KELAS VIII SMP NEGERI 3 BOJONEGORO ). - Siti Patonah, Siti Patonah; Atik S, Atik S; Ima Elly, Ima Elly (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2013)
Breast tumors is an abnormal lump in the breast . In 2002 there was 1 student who had breast cancer and a preliminary survey of 20 students , 12 students have learned and experienced anxiety breast tumors . The purpose of this study was to analyze the relationship of knowledge about breast tumors with anxiety in adolescent girls            This research uses analytic design with cross sectional approach . Total population of 95 respondents , 77 respondents sampled using a sampling technique of simple random sampling . The independent variable knowledge about young women and breast tumors dependent variable is the teenage anxiety about breast tumors . Methods of data collection using questionnaire and then collecting data editing , coding , scoring , tabulating and then conducted data analysis using Spearman 's rho correlation test .             The results of the study using SPSS nonparametric Spearman 's rho values obtained ? = 0.05 correlation coefficient - , 356 in the direction parallel to the negative correlation in the opposite direction and the two tiailed significant value 0.002 . Thus , Ho is rejected and the obtained value of correlation coefficient - , 364 in the direction parallel to the negative correlation in the opposite direction and the two tiailed significant value of 0.001 . Thus , Ho is rejected .             From the above results it is concluded that there is a relationship of knowledge to know the stage , the notion of breast tumors with anxiety in adolescent girls in Junior High School eighth grade 3 Bojonegoro , caused no knowledge factors , age and education are sufficient . It is expected that young women could increase knowledge about breast tumors with reading in the library and look for information on the Internet , and given an education about the importance of knowledge of breast    tumors. . Keywords : Knowledge , breast tumors and anxiety